Biceps Tenodesis and Intra-articular Decompression for Treatment of Superior Labral Tear from Anterior to Posterior and Associated Paralabral Cyst in Active Duty Military. Issue 5 (6th February 2018) - Perry, Nicholas P J; Wolfe, Jared A; Nguyen-Ta, Kim; Christensen, Daniel; McDonald, Lucas S; Dickens, Jonathan F; LeClere, Lance E
Abstract: Background: To examine the outcomes of combined biceps tenodesis and indirect, intra-articular arthroscopic paralabral cyst decompression for the treatment of active duty military patients with superior labral from anterior to posterior tears and associated paralabral cysts. Methods: Retrospective chart review of all active duty patients at our institution from 2011 to 2014 with superior labral from anterior to posterior tears and associated paralabral cysts at the spinoglenoid notch treated with biceps tenodesis and indirect arthroscopic cyst decompression. Patient charts were examined for pre- and post-operative parameters including strength, range of motion, visual analog scale pain score, American Shoulder and Elbow Surgeon Score, and Single Assessment Numeric Evaluation Score. Results: Seven patients met study criteria. All patients presented with chronic shoulder pain and decreased external rotation strength, and three patients had clinically apparent muscular atrophy. Pre- and post-operative assessment showed external rotation strength increased from a median of 4 (range 4–4) to 5 (range 4–5; p -value = 0.014), Single Assessment Numeric Evaluation increased from a median of 50 (range 0–70) to 75 (range 30–95; p -value = 0.031), American Shoulder and Elbow Surgeon increased from a median of 46.0 (range 32.0–58.0) to 66.5 (range 58.0–98.0; p -value = 0.068), and visual analog scale pain score decreased from a median of 3 (range 1–8) to 0 (range 0–5; p -value = 0.017). Median follow-up was 66 wk (range 36–138 wk). The change was statistically significant ( p <0.05) for external rotation strength, Single Assessment Numeric Evaluation, and VAS reduction. Post-operatively, all patients returned to full duty at a median of 20 wk (range 12–36 wk). Conclusion: The use of biceps tenodesis in conjunction with indirect, intra-articular arthroscopic paralabral cyst decompression is an effective technique in an active patient population with superior labral from anterior to posterior tear with associated paralabral cyst.